The hair-trigger effect for a class of nonlocal nonlinear equations. (20th April 2018) - Finkelshtein, Dmitri; Tkachov, Pasha
Abstract: We prove the hair-trigger effect for a class of nonlocal nonlinear evolution equations on which have only two constant stationary solutions, 0 and . The effect consists in that the solution with an initial condition non identical to zero converges (when time goes to ) to θ locally uniformly in . We also find sufficient conditions for existence, uniqueness and comparison principle in the considered equations.